ST Hydrogeological and Geophysical Characterization of Kozlupınar and Bentpınarı Water Springs (Denizli, SW Turkey) - Tasdelen, Suat (IJRDO-Journal of Applied Science, 2019)
This study focusses on describing the hydrodynamic interactions of the Kozlupınar - Bentpınarı springs, aquifer units, groundwater, water table, Babadağ fault zone, and topography, with each other. Due to rapid urbanization and increasing population densities in Denizli, the safe water supply becomes more and more difficult every day. Kozlupınar and Bentpınar springs are historically significant water supply sites for Denizli city. Although the expansion of the city has resulted in the destruction of numerous springs, both springs are still in their natural state, and have great value for urban use in Denizli and vicinity. Kozlupınar’s average flow is 0,100 m3/s; Bentpınarı is 0.130 m3/s. The average base flows calculated using the Maillet equation (1977-1979) are to 4.75×106 m3/year, and 7.41×106 m3/year respectively. The spring variability estimated as 0.22 for Kozlupınar and 0.12 for Bentpınarı . Recession coefficients, to 0.00199 days−1, and 0.00109 days−1 respectively. The spring waters emerge from sediments that accumulate on the slopes of the southern mountainous terrain along the Babadağ fault. Hydrologic process of the groundwater, start by the infiltration of precipitation on the high hills on the north side of the Babadağ fault. Almost all aquifers in the region, which feeds springs, and extends to wider areas outside the study area, is heterogeneous and anisotropic due to the different origins and tectonic forces affecting the region. Groundwater flows from south and south-west highland parts of the catchment towards the springs areas in the north and northeast direction.